Enhancing Jerk Nonlinear Equation by Adomain Decomposition Method (Journal of Nonlinear Modeling and Analysis, 2025)
In this manuscript, an approximate periodic solution of a nonlinearJerk equation concerning the third order time derivative (ODE) is demonstrated. This method succeeds highly in constructing a periodic solutionfor Jerk nonlinear differential equations. The results investigated from thismethod are compared with those determined from other analytical and numerical methods. Our results demonstrate a significant consistency with thenumerical solution in addition to the analytical methods.
Keywords: Adomian decomposition method; nonlinear Jerk equation; high order differential equation.